Remodeling of retrotransposon elements during epigenetic induction of adult visual cortical plasticity by HDAC inhibitors. Issue 1 (December 2015) - Lennartsson, Andreas; Arner, Erik; Fagiolini, Michela; Saxena, Alka; Andersson, Robin; Takahashi, Hazuki; Noro, Yukihiko; Sng, Judy; Sandelin, Albin; Hensch, Takao; Carninci, Piero
Abstract Background The capacity for plasticity in the adult brain is limited by the anatomical traces laid down during early postnatal life. Removing certain molecular brakes, such as histone deacetylases (HDACs), has proven to be effective in recapitulating juvenile plasticity in the mature visual cortex (V1). We investigated the chromatin structure and transcriptional control by genome-wide sequencing of DNase I hypersensitive sites (DHSS) and cap analysis of gene expression (CAGE) libraries after HDAC inhibition by valproic acid (VPA) in adult V1. Results We found that VPA reliably reactivates the critical period plasticity and induces a dramatic change of chromatin organization in V1 yielding significantly greater accessibility distant from promoters, including at enhancer regions. VPA also induces nucleosome eviction specifically from retrotransposon (in particular SINE) elements. The transiently accessible SINE elements overlap with transcription factor-binding sites of the Fox family. Mapping of transcription start site activity using CAGE revealed transcription of epigenetic and neural plasticity-regulating genes following VPA treatment, which may help to re-program the genomic landscape and reactivate plasticity in the adult cortex. Conclusions Treatment with HDAC inhibitors increases accessibility to enhancers and repetitive elements underlying brain-specific gene expression and reactivation of visual cortical plasticity.